ANALISIS LAPORAN KEUANGAN DALAM RANGKA MENENTUKAN TINGKAT KESEHATAN BUMN (Studi Kasus Pada PT PLN APJ KUDUS) - Aida Nahar; Dwi Santoso (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractFinance report analisys is one of alternative to intepretated healthy company finance level. The Scription use to know and analys healthy company finance level PT. PLN Net and Service Area (APJ) Kudus with based to decision letter of Republic Indonesia  Finance Ministary No. 8241 KMK. 01311992.The research have to use rentability, liquidity, and solvability analisys (main indicator) toevaluated healthy company finance  level, beside that it have to use  added indicator are profit margin ratio, operational ratio and conected result level ratio.The evaluation healthy finance company level had to use dates from 1999-2003 years that to compare with decision letter of Republic Indonesia Finance Ministary No. 824/KMK. 0131 1992. The research result was interpretation healthy company level PT. PLN APJ Kudus that showed rentability level is very good, as big as 127,07 %,for liquidity level and solvability level are 523,18 % and 514,9%. After evaluated was rentability, liquidity, and solvability level show finance  with very good condition. Keywords: Finance report,company finance level, rentability, liquidity, solvability